2013
DOI: 10.5141/ecoenv.2013.167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different densities of wild oat (Avena fatua L.) and nitrogen rates on oilseed rape (Brassica napus L.) yield

Abstract: A Two-year field experiment was carried out in 2009 and 2010 to evaluate the effects of different densities of wild oat and nitrogen (N) rates on oilseed rape yield and yield components. Experimental design was split plot with three replications. Increased nitrogen rates up to 150 kg N/ha caused an increase in oilseed rape grain yield in weed-free plots (4.26 t/ha; 1t = 10 3 kg), while even at the lowest density of wild oat (15 plants/m 2 ), increasing N fertilizer only up to 50 kg/ha led to a significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Particularly, N application up to 36 kg N ha −1 increased multiple-weed competitiveness to soybean, resulting in a significant yield loss more than 89% at 12 plants m −2 of the total density equivalent (Figure 3). Previous studies also indicated that N fertilizer increases weed competitiveness against crops including rice [11], wheat [14,29] and oilseed rape [30]. The N effect on weed competitiveness with crops might be dependent on interference relationships, since N application changes both crop growth and weed biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, N application up to 36 kg N ha −1 increased multiple-weed competitiveness to soybean, resulting in a significant yield loss more than 89% at 12 plants m −2 of the total density equivalent (Figure 3). Previous studies also indicated that N fertilizer increases weed competitiveness against crops including rice [11], wheat [14,29] and oilseed rape [30]. The N effect on weed competitiveness with crops might be dependent on interference relationships, since N application changes both crop growth and weed biomass.…”
Section: Discussionmentioning
confidence: 99%
“…In poor soils, yields improve with the application of nutrients, especially nitrogen, phosphorus and potassium, which clearly promote plant growth. However, some authors indicate that such applications benefit weeds more so than crops, increasing the farmers' negative impact [11]. In situations in which nutrient supply is limited, some weeds can absorb greater quantities of nitrogen.…”
Section: Factors Involved In Competition Between Crops and Weedsmentioning
confidence: 99%
“…Water greatly affects sterile oat growth and development [14]. Recent research on weeds in response to climate change has suggested that focusing on drought-resistant weed biotypes is of great importance [15], as the different responses of herbicide-resistant and susceptible biotypes of a weed species to climatic changes may influence their fitness and population dynamics [16][17][18].…”
Section: Introductionmentioning
confidence: 99%